Assessing public-private partnerships for small ruminant flock health service delivery in Ethiopia - Lemma, Mamusha; Temesgen, Wudu; Fatalo, T.; Yitagesu, E.; Knight-Jones, Theodore J.D. (2024)
In Ethiopia, animal health services face several challenges, including limited access to veterinary supplies, inadequate infrastructure and resource constraints, which negatively impact livestock health and farmers’ livelihoods. To address these issues, public-private partnership (PPP) models have been introduced, leveraging both public and private sector resources to provide more accessible and efficient animal health services. Since 2022, the CGIAR Initiative on Sustainable Animal Productivity (SAPLING) has piloted a PPP model in two communities, focusing on preventive health services and training and advisory services for small ruminant farmers to showcase its potential in improving veterinary services. The intervention design concentrated on these services as entry points to demonstrate the potential of PPP arrangements to provide extended animal health services beyond the pilot test. The pilot test has a limited focus on preventive health services for small ruminants, service discounts for participating households, negotiated service prices, and training and advisory services. It was anticipated that this pilot testing of the PPP arrangement would lead to sufficient demands from farmers and private service providers for ongoing, expanded service partnerships across various livestock species, transitioning to a full-cost, sustainable model.